Aesthetic complacency and satisfaction of will in Schopenhauer's metaphysic of the beauty - Salviano, Jarlee Oliveira Silva (2019)
Following in the footsteps of Kant, Schopenhauer builds his Metaphysics of the beauty from the conception of art “disinterested”. Knowledge determined by motives gives to the spectator of art the “exciting” and the mere empirical satisfaction, but not the beauty or the sublime. The Genius, most potent and effective representation of the Pure Subjectivity of Knowledge is described in the Book III of The world as will and representation in an apparently ambiguous way: as the Willenlos (free of will), like that free of the storm of the passions and the impetus of desires. But at the same time as that subjected to vehement affections and irrational passions. However, it is, in the aesthetic experience of the genius or the contemplator of art, a disinterested pleasure, a complacency of another order than that of the man of common sense and science. The article then seeks to analyze Schopenhauer’s concept of aesthetic complacency or satisfaction and its roots in Kant’s philosophy.